2D Molybdenum Compounds for Electrocatalytic Energy Conversion. (23rd November 2022) - Chen, Jianmei; Lin, Yanping; Wang, Hao; Li, Jianmin; Liu, Shujuan; Lee, Jong‐Min; Zhao, Qiang
Abstract: The development of advanced nanomaterials is urgent for electrocatalytic energy conversion applications. Recently, 2D nanomaterial‐derived heterogeneous electrocatalysts have shown great promise for both fundamental research and practical applications owing to their extremely high surface‐to‐volume ratio and tunable geometric and electronic properties. Because of their unique electronic structure and physicochemical properties, molybdenum (Mo)‐based 2D nanomaterials are emerging as one of the most attractive candidates among the nonprecious materials for electrocatalysts. This review provides a comprehensive overview of the recent advances in the synthesis and modulation of 2D Mo compounds for applications in electrocatalytic energy conversion. The categories based on different compositions and corresponding synthetic approaches of 2D Mo compounds are first introduced. Subsequently, various atomic/plane/synergistic engineering strategies, along with catalytic optimization in the electrochemical process that involves the cycles of water, carbon, and nitrogen, are discussed in detail. Finally, the current challenges and future opportunities for the development of 2D Mo‐based electrocatalysts are proposed with the goal of shedding light on these promising 2D nanomaterials for electrocatalytic energy conversion. Abstract : 2D molybdenum compounds, by virtue of their high surface‐to‐volume ratio, unique electronic structure, and physicochemical properties, show great potential in electrocatalytic energy conversion applications. This review provides a comprehensive overview of the strategies for the synthesis and modulation of 2D molybdenum compounds and their applications in various electrocatalytic reactions that involve the cycles of water, carbon, and nitrogen.